PREVALENCE AND PUBLIC PERCEPTION OF GASTROINTESTINAL PARASITES IN SELECTED EDIBLE FRUITS AND VEGETABLES SOLD IN EKPOMA MARKETS, EDO STATE - Akinnubi, Taiwo Joshua; Irabor, Precious Osarugue; Egede-Auselimen, Jeninifer Oghogho (FUDMA JOURNAL OF SCIENCES, 2025)
Fruits and vegetables are essential components of healthy diet because of their high nutritional and antioxidative properties, but could also constitute risk to human health when consumed unclean. This study assessed the prevalence and public perception of gastrointestinal parasites in commonly consumed fruits and vegetables sold in Ekpoma Markets, Edo State, from September to December 2024. A Total of 150 fruits and vegetable samples were randomly purchased from three selected markets (Ekpoma Main Market, Iruekpen Market and Opoji Market). The samples were analysed using sedimentation technique and examined microscopically for parasitic contamination. Structured questionnaires were administered to gather data on knowledge, hygiene practices and healthcare-seeking behaviour of the vendors. Data were analysed using descriptive statistics and Chi-square tests. The results revealed an overall prevalence rate of 64.7%, with vegetables exhibiting a higher contamination rate (70.7%) compared to fruits (58.7%). Iruekpen Market recorded the highest contamination rate (76.0%). Five gastrointestinal parasites were detected: Ascaris lumbricoides, hookworm, Strongyloides spp., Trichuris trichiura and coccidia, with hookworm being the most prevalent (31.3%). Public awareness of the potential for contamination was high, with 93.33% of respondents acknowledging the risk. However, many of the participant still relied on traditional treatment methods rather than seeking medical care. More than half of participants, (56.7%), reported regular deworming every few months. This study highlights the need for improved public health education on produce hygiene and emphasize the use of medical care over traditional remedies. Implementation of better sanitation practices in produce markets and encouragement of regular deworming are...